Nicość realna w interpretacji Heideggera, Sartre'a, Weltego, Nehera i filozofów Bliskiego i Dalekiego Wschodu - Ochmann, Jerzy (Poznańskie Studia Teologiczne, 2009)
Nothingness is a multifaceted problem. The basic difficulty connected with it emerges in the philosophy of language, as it hardly possible to name and find an appropriate term for that which does not exist. The problem proper arises when we are to justify nothingness, to support its fact in a rational, and at least partly, also in a scientific mode. Reflection on nothingness is taken up today in six cultures: in the philosophical thought of the West (Heidegger, Sartre, Welte, Neher), in Jewish theology, in Christian theology, and in Hinduistic, Buddhist and Taoistic thought. In each of those traditions the issue of nothingness is associated with a different context. In the West it is considered philosophically in ontology, where it serves to explain the problem of being (Heidegger) or to contradict what is considered as being (Nietzsche). In theology nothingness manifests itself in several contexts: in connection with the doctrine of creation out of nothingness (creatio ex nihilo), where it appears as that which did not exist previously or as that which might have existed but from a later perspective is defined as nothingness “with respect to what is at present” and when God is considered to be Nothingness.